The features and risk factors of thrombotic thrombocytopenic purpura in systemic lupus erythematosus - Hang Ma; Yujie He; Shanshan Li; Yingchao Yang; Liubin Huo; Tianfang Li (Orphanet Journal of Rare Diseases)
Abstract Objective This study aimed to investigate clinical features and risk factors for the development of thrombotic thrombocytopenic purpura (TTP) in systemic lupus erythematosus (SLE) patients. Methods A cohort of 32 SLE-TTP patients in the first affiliated hospital of Zhengzhou University from 2017 to 2023 were included, and 128 SLE patients without TTP admitted to the hospital during the same period were randomly selected as the control group. The demographic data, clinical and laboratory findings of these patients were statistically analyzed. Stepwise regression and logistic regression were used to identify the risk factors related to TTP development. The SLE-TTP patients were divided into two groups based on treatment outcomes, and the differences between the clinical data were compared between the two groups. Independent risks of short-term death in SLE-TTP patients were determined by logistic regression analysis. Results Our study demonstrated that independent risk factors associated with the occurrence of TTP in patients with SLE included higher SLEDAI-2K score (OR = 1.96; 95%CI: 1.197–3.211; P = 0.007), high baseline total cholesterol (T-CHO) levels (OR = 8.19; 95%CI: 0.98–68.48; P = 0.048), and renal involvement (OR = 14.73; 95%CI: 1.250-173.64; P = 0.033). Multivariate logistic regression analysis showed that older age (OR = 1.02;95%CI: 0.94–1.119; P = 0.05) and non-nulliparous female (OR = 8.12; 95%CI: 0.484-136; P = 0.017) were independent risks factor for short-term death for SLE-TTP patients. Conclusion SLE patients with higher SLEDAI-2K score, high baseline T-CHO levels, and renal involvement were predisposed to TTP development. The short-term mortality is increased for SLE-TTP patients of advanced age and in non-nulliparous females. Close monitoring and active treatments of these patients are needed for this life-threatening situation.